IMPLEMENTASI PERMENDIKBURISTEK NO. 30 TAHUN 2021 TENTANG PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI LINGKUNGAN PERGURUAN TINGGI (STUDI DI UNIVERSITAS ISLAM MALANG) - As'adur Rifqi (Dinamika, 2023)
ABSTRACTIn this thesis, the author raises the title of the thesis Implementation of PermendikbudRISTEK No. 30 of 2021 regarding the prevention and handling of sexual violence in theuniversity environment (Study at the Islamic University of Malang) with the followingproblem formulation: 1. How is the Implementation of Permendikbud RISTEK No. 30 of 2021concerning Prevention and Handling of Sexual Violence in Higher Education (Study at theIslamic University of Malang) ? 2. What are the obstacles to the implementation ofPermendikbud RISTEK No. 30 of 2021 concerning the Prevention and Handling of SexualViolence in Higher Education (Study at the Islamic University of Malang)?The research method that the author uses is empirical juridical and uses a sociologicaljuridical approach. The legal data used are primary legal data, namely observations andinterviews, secondary legal data in the form of various kinds of literacy books and tertiarylegal materials in the form of dictionaries.The results of the study regarding the obstacles to the implementation of PermendikbudRISTEK No. 30 of 2021 concerning the Prevention and Handling of Sexual Violence inHigher Education (Studies at the Islamic University of Malang) is overall, the Decree of theChancellor of the Islamic University of Malang which contains guidelines, the formation of aselection committee, and the establishment of a Task Force for the Prevention and Handlingof Sexual Violence. Permendikbud RISTEK No. 30 of 2021 concerning the Prevention andHandling of Sexual Violence in Higher Education. However, in terms of implementation, itcan be said that it is still not optimal or still not effective due to the obstacles faced by theIslamic University of Malang.Keywords : Permendikbud, Sexual Violence, UniversitiesABSTRAKDalam skripsi ini, penulis mengangkatjudul skripsiImplementasiPermendikbudRISTEK no 30 tahun 2021 tentang pencegahan dan penanganan kekerasanseksual di lingkungan perguruan tinggi (Studi di Universitas Islam Malang) dengan rumusanmasalah sebagaimana berikut : 1. Bagaimana Implementasi Permendikbud RISTEK No. 30Tahun 2021 tentang Pencegahan dan Penanganan Kekerasan Seksual di LingkunganPerguruan Tinggi (Studi di Universitas Islam Malang) ? 2. Apa faktor kendala ImplementasiPermendikbud RISTEK No. 30 Tahun 2021 tentang Pencegahan dan Penanganan KekerasanSeksual di Lingkungan Perguruan Tinggi (Studi di Universitas Islam Malang)?Metode penelitian yang penulis gunakan adalah yuridis empiris dan menggunakanpendekatan yuridis sosiologis. Data hukum yang digunakan adalah data hukum primer yakniobservasi dan wawancara, data hukum sekunder yang berupa berbagai macam buku literasidan bahan hukum tersier yakni berupa kamus.Hasil penelitian mengenai kendala Implementasi Permendikbud RISTEK No. 30 Tahun2021 tentang Pencegahan dan Penanganan Kekerasan Seksual di Lingkungan PerguruanTinggi (Studi di Universitas Islam Malang) adalah secara keseluruhan, Keputusan RektorUniversitas Islam Malang yang memuat tentang Pedoman, Pembentukan Panitia Seleksi,danPembentukan Satuan Tugas Pencegahan dan Penanganan Kekerasan Seksual sudah sesuaidengan Permendikbud RISTEK No. 30 Tahun 2021 tentang Pencegahan dan PenangananKekerasanSeksual di Lingkungan Perguruan Tinggi. Namun dalam halpengimplementasiannya dapat dikatakan masih belum optimal atau masih belum efektifdikarenakan adanya kendala yang di hadapi oleh Universitas Islam Malang.Kata Kunci : Permendikbud, Kekerasan Seksual, Perguruan Tinggi